Mobile application and traditional approach for Chinese stroke order instruction in foreign language classroom / Ting Hie-Ling, Ch’ng Looi-Chin and Norseha Unin - Ting, Hie-Ling; Ch’ng, Looi-Chin; Unin, Norseha (Universiti Teknologi MARA, Perlis, 2020)
Learning to write Chinese characters in the correct stroke order is important. However, it is rather challenging for learners especially non-native learners due to the complicated structures and the diversity of Chinese characters. Traditionally, rote learning has perceived as the most preferred used learning strategy in Chinese characters and it is highly recommended for the learners. Nonetheless, the rapid development of technology has changed the mode of learning. Mobile applications are utilized as media learning as it provides more opportunities for learners to learn everywhere and at anytime. This paper aims to investigate the impact of mobile app (MAs) and traditional method on Chinese characters stroke order learning. 100 students from the Faculty of Business and Management at UiTM (Sarawak), Mukah campus have been selected as participants for this study. The findings reported that both methods are able to help participants to pass the tests but the difference of both impacts is small. Although, the differences are not huge, but it is significant to tell mobile application might provide a better outcome compared to traditional method.